Finding the Composition of Functions
To find the composition of two functions, we denote it as (f ∘ g)(x), which means we will substitute g(x) into f(x).
Step 1: Identify the Functions
We have the following two functions:
- f(x) = 3x² + 2
- g(x) = 5x² + 1
Step 2: Substitute g(x) into f(x)
We want to find (f ∘ g)(x) = f(g(x)). This means we will plug g(x) into f(x).
So:
- g(x) = 5x² + 1
Substituting g(x) into f(x):
f(g(x)) = f(5x² + 1) = 3(5x² + 1)² + 2
Step 3: Expand the Expression
Now we need to expand (5x² + 1)²:
(5x² + 1)² = 25x^4 + 10x² + 1
Next, we substitute this back into f(g(x)):
f(g(x)) = 3(25x⁴ + 10x² + 1) + 2
Step 4: Distribute the 3
Now we distribute 3 into the expanded expression:
3(25x⁴) + 3(10x²) + 3(1) + 2 = 75x⁴ + 30x² + 3 + 2
Step 5: Combine Like Terms
Finally, combine the constants:
75x⁴ + 30x² + 5
Final Result
The composition of the functions f and g is:
(f ∘ g)(x) = 75x⁴ + 30x² + 5
And that’s how you find the composition of the functions step by step!